Protective effects of taurine against nicotine-induced oxidative damage of rat urinary bladder and kidney - ŞENER, GÖKSEL (KARGER, 2005)
Several studies demonstrate that taurine treatment prevents tissue damage in various models of inflammation. Experiments have shown that chronic nicotine administration caused oxidant damage in various organs by increasing lipid peroxidation products and decreasing the activity of endogenous antioxidants. The aim of this study was to investigate the effects of taurine treatment on nicotine-induced oxidative changes in rat urinary bladder and kidney and to explore the possible mechanisms of action. Male Wistar albino rats were injected with nicotine hydrogen bitartrate (0.6 mg/kg i.p.) or saline for 21 days. Taurine was administered ( 50 mg/kg i.p.) alone or along with nicotine injections. At the end of the treatment period bladder tissue was used for in vitro contractility studies, or stored along with kidney tissue for the measurement of malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and collagen content. Tissue samples were also examined histologically. Serum samples were stored for the measurement of MDA, GSH, blood urea nitrogen, creatinine and lactate dehydrogenase activity. Chronic nicotine treatment decreased the contractile activity of the bladder strips to carbachol and increased lipid peroxidation, MPO levels and tissue collagen content of the bladder and kidney samples. Taurine supplementation to nicotine-treated animals reversed the contractile dysfunction of the bladder strips. It also preserved the renal functions, restored the endogenous GSH levels and decreased high lipid peroxidation and MPO activities in both urinary bladder and kidney tissues. These data suggest that taurine supplementation effectively counteracts the deleterious effect of chronic nicotine administration on bladder and kidney functions and attenuates oxidative damage possibly by its antioxidant effects. Copyright (C) 2005 S. Karger AG, Basel.
Keywords: taurine; nicotine; oxidative damage; urinary bladder; kidney; INFLAMMATORY MEDIATORS; NITRIC-OXIDE; IN-VITRO; CHLORAMINE; GENERATION; MYELOPEROXIDASE; NEUTROPHILS